Vostochnyĭ beregʺ poluostrova Kamchatki otʺ mysa Lopatka do mysa Sīamo po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana sʺ 1910 po 1919 godʺ / Chertili Sht. d. pl. P. Simonʺ i Kap. m. pl. V. Gragaĭtisʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : [Морское министерство, Главное гидрографическое управленіе], 1919)
Title translation: Eastern coast of the Kamchatka Peninsula from Cape Lopatka to Cape Siamo, according to the survey of the Hydrographic Expedition of the Eastern Ocean from 1910 to 1918.; Relief shown by form lines, hachures and spot heights. Depths shown by soundings and isolines.; Includes table of coordinates; Greenwich meridian Grayscale; 1:219,156